PROGRAMMING OF THE VARIABLE FITNESS MODULE (ZUMBA STRONG) IN THE HOMEWORK SYSTEM FOR PHYSICAL EDUCATION FOR HIGH SCHOOL GIRLS (Physical Culture and Sport: Scientific Perspective, 2024)
Since the beginning of the New Ukrainian School reforms, positive and qualitative changes have been observed. One of the innovations of the NUS is a model curriculum that aims to develop the physical qualities of schoolchildren by including variable modules in various sports.            The scientific article substantiates the conceptual approach to the organization of the educational process using the elements of "Zumba strong" as a variable module for high school students. It has been experimentally proved that the purposeful use of "Zumba strong" tools in physical education lessons provides a significant improvement in the components of the physical condition of high school students. The research is devoted to the development of a variable fitness module with elements of "Zumba strong" and the use of interval functional training for high school girls in physical education classes. The developed variable module can be used in the future to form modern methods of competency-based learning and new educational technologies in the context of the New Ukrainian School. The practical developments were implemented in the educational process of a general secondary education institution, as well as in the professional development courses for teachers.            The results of the pedagogical experiment on the implementation of the variable module "Zumba Strong" convincingly testify to its effectiveness and allow us to state that the proposed tools had a positive impact on both the correction of body weight of high school girls and the formation of a harmonious body structure. The "Zumba Strong" products provided a significant increase in the results of the cardiorespiratory system in the participants of the experiment and thus contributed to the improvement of its reserve capacity.
Keywords: physical activity; fitness equipment; variable module; physical education lesson